Innovative Kommissionier- und Umschlagkonzepte der Logistik - der fachliche Ansatz des Forschungsprojektes ADINA - Tim Gruchmann; Matthias Klumpp; Thomas Hanke; Kristina Nestler (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2018)
– Logistics commands a huge variety of dynamic developments, driven by technological, organizational as well as market changes. In this regard, logistics management requires innovations to meet this dynamic environment. In particular automation is seen as promising way to tackle potentials for economical, eco-logical and social sustainability. The publication of this research paper marks the start of the project 'ADINA', which does encompass the development of innovative warehousing and picking strategies. While the main focus of the project work is to increase competitiveness of the participating companies, the project follows an action research approach. This approach ensures that all steps from problem identification, conceptualization, problem solving and implementation are made transparent and consider the feedback from previous steps. This research paper describes the overall project methodology of con-ducting action research and documents the first phase of problem identification. The paper is structured as follows: Section 1 introduces the project aim, while section 2 contains a review of relevant trends influencing the companies' environment. Section 3 provides a brief summary of related research activities and industry projects, while section 4 describes the applied methodological approach of action research. Section 5 and 6 document the first phase of problem identification and transfer, and finally section 7 provides an outline of upcoming milestones in the project ADINA.
Keywords: 650